Factors associated to first line antiretroviral therapy (ART) failure among HIV/AIDS patients at Sanglah Hospital, Bali - Cok Istri Sri Dharma Astiti; Anak Agung Sagung Sawitri; Ketut Tuti Parwati Merati (Universitas Udayana, 2017)
Background and purpose: The incidence of first line ART failure is increasing in the South East Asia region. The main referral hospital in Bali has recorded an increased use of second line ART due to the first line ART failure. This study aims to explore risk factors associated to first line ART failure. Methods: A case control study was conducted among people living with HIV and AIDS at Sanglah Hospital Denpasar who started first line ART between 2004 and 2013. Cases were those who diagnosed as having clinical treatment failure and still on treatment in 2015. Controls were those with no treatment failure. Sex and year of ART initiation were matched between case and control. Data were obtained from medical records that include initial regiments, HIV mode of transmission, the WHO HIV clinical stage, CD4 count, opportunistic infections, body mass index, hemoglobin level, and drug substitution at the beginning and during treatment. Risk factors were analysed using logistic regression. Results: Out of 68 HIV/AIDS patients with clinical ART failure, 72.1% were confirmed with immunological and 36.8% were confirmed with virological failure. Median time before treatment failure was 3.5 years. Factors associated to ART failure were HIV clinical stage IV (AOR=3.43; 95%CI: 1.65-7.13) and being widow/widower (AOR=4.85; 95%CI: 1.52-15.53). Patients with TB co-infection have a lower risk for treatment failure due to early diagnosis and treatment through TB-HIV program (AOR=0.32; 95%CI: 0.14-0.70). Conclusions: Higher HIV clinical stage at ART initiation increases the risk of treatment failure. HIV-TB co-infection indirectly reduces the risk of treatment failure.